1972
DOI: 10.1073/pnas.69.5.1151
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence of Lysozyme: Emissions from Tryptophan Residues 62 and 108 and Energy Migration

Abstract: The bulk of the fluorescence of lysozyme is located in Trp 62 and Trp 108. By examination of the fluorescence of derivatives in which Trp 62 and/or Trp 108 are specifically oxidized, it has been possible to detect a pH-dependent interaction between tryptophan residues. This interaction is interpreted as energy transfer from Trp 108 to Trp 62.The efficiency of tryptophan fluorescence in proteins varies widely from one protein to another, with quantum yields ranging from about 0.025 to greater than 0.4 (1). In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
169
0
1

Year Published

1975
1975
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(176 citation statements)
references
References 18 publications
6
169
0
1
Order By: Relevance
“…The normalized fluorescence changes versus the different incubation time appeared almost the same for the emission spectra obtained from excitation at 280 and 295 nm (data not shown), indicating that the quenching of fluorescence can be attributed to Trp residues. Taken together with the fact that Trp62 is one of the two dominant emitters (the other is Trp108), 56 the binding site which is located close to Trp62, identified by the docking study, is very likely to be the real scenario. This is consistent with previous investigations in which certain small molecules with inhibitory activity toward HEWL fibril formation, such as EGCG, EUK-8, and EUK-134 (two kinds of salen−manganese complexes) were also suggested to bind to Trp62 and Trp63 in docking studies.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The normalized fluorescence changes versus the different incubation time appeared almost the same for the emission spectra obtained from excitation at 280 and 295 nm (data not shown), indicating that the quenching of fluorescence can be attributed to Trp residues. Taken together with the fact that Trp62 is one of the two dominant emitters (the other is Trp108), 56 the binding site which is located close to Trp62, identified by the docking study, is very likely to be the real scenario. This is consistent with previous investigations in which certain small molecules with inhibitory activity toward HEWL fibril formation, such as EGCG, EUK-8, and EUK-134 (two kinds of salen−manganese complexes) were also suggested to bind to Trp62 and Trp63 in docking studies.…”
Section: ■ Discussionmentioning
confidence: 99%
“…All measurements were carried out at 25°C at a lysozyme concentration of 0.3 mg/mL in the presence of the desired concentration of the salts at pH 5.1. Lysozyme fluorescence emission (with a maximum of 340 nm) mainly stems from two buried Trp residues when excited selectively at 284 nm (Imoto et al, 1971).…”
Section: Fluorescence Measurementsmentioning
confidence: 99%
“…The contribution of individual lysozyme Trp residues to the fluorescence emission spectrum has been studied in detail by chemical modification and fluorescent lifetime measurement studies (Imoto et al, 1971;Formoso & Forster, 1975). Their studies found that Trp 62 and Trp 108 contribute most of the fluorescence emission of native lysozyme.…”
Section: Discussionmentioning
confidence: 99%